Functional evaluation of TERT-CLPTM1L genetic variants associated with susceptibility of papillary thyroid carcinoma - Ge, Minghua (Sci Rep, 2016)
TERT is the catalytic subunit of telomerase which plays an essential part in cellular immortality by maintaining telomere integrity. TERT is commonly over-expressed in human malignancies, indicating its key role in cell transformation. The chromosome 5p15.33 TERT-CLPTM1L region has been associated with susceptibility of multiple cancers via a genome-wide association approach. However, the involvement of this locus in papillary thyroid carcinoma (PTC) etiology is still largely unknown. We analyzed 15 haplotype-tagging single nucleotide polymorphisms (htSNPs) of the TERT-CLPTM1L region in a two stage case-control design. After genotyping 2300 PTC patients and frequency-matched 2300 unaffected controls, we found that TERT rs2736100 genetic variant is significantly associated with elevated PTC risk. Ex vivo reporter gene assays indicated that the PTC susceptibility rs2736100 polymorphism locating in a potential TERT intronic enhancer has a genotype-specific effect on TERT expression. Correlations between rs2736100 genotypes and tissue-specific TERT expression supported the regulatory function of this genetic variant in vivo. Our data demonstrated that the functional TERT rs2736100 SNP as a novel genetic component of PTC etiology. This study, together with recent studies in other cancers, unequivocally establishes an essential role of TERT in cancers.